Números en clave femenina: aproximación desde los estudios visuales - Azanza López, José Javier (Anuario de historia de la Iglesia, 2022)
Within the «gender silence» characteristic of the Bible, the Book of Numbers, despite its decided androcentricity, contains several passages with a female presence (Mary and the Cusite wife of Moses, the death of Mary, the Moabites and the Midianite Cozbí, the inheritance of the daughters of Selofjad) that analyze questions about the leadership over the Jewish people, the iron patriarchal control exercised by Hebrew legislation, the femicide and the unequal treatment between men and women in matters such as sin and death. This paper proposes an approach from visual studies, in permanent dialogue with the biblical story, exegesis and the most recent lines of research.